Online Media Management In Using Social Media Facebook - Falimu, Falimu; Karinda, Kisman (Devotion : Journal of Research and Community Service, 2022)
This research is about how online media management sangalu.com in using Facebook social media to be able to provide information that is received by a wide audience. Online media management in this case sangalu.com will describe several management functions in using Facebook as a communication medium, including management functions, namely planning, organizing, implementing, and monitoring, the use of Facebook social media. Research findings with the application of management functions to ensure continuity between the facts in the field and the management functions carried out. In its development, the online media sngalu.com has implemented this management function, although some things have not been applied optimally. In this study, the researcher used a qualitative descriptive methodology where the researcher tried to review the online media management activities that had been carried out by sangalu.com using predetermined data collection the paradigm used was the constructivism paradigm, the right paradigm in this study where researchers tried to see what was being done. sangalu.com party carries out the management process with various forms of its functions, in managing social media Facebook